2010
DOI: 10.1038/nrneph.2010.103
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular diseases: genetic causes and future therapeutics

Abstract: The glomerulus consists of capillary tufts, a mesangial cell component and the Bowman capsule. The glomerular filtration barrier is composed of glomerular endothelial cells, a basement membrane, and podocytes. Particular components of the slit diaphragm and the glomerular basement membrane strictly orchestrate the integrity of the glomerular filtration barrier. The basement membrane is made of a highly crosslinked macromolecular meshwork of type IV collagen, proteoglycans, and laminin. Genetic forms of glomeru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 167 publications
0
59
0
Order By: Relevance
“…45 Mutations of actin-binding proteins, such as a-actinin-4 or CD2AP, lead to podocyte injury because of disorganization of the actin cytoskeleton and disruption of its filtration barrier. 41,46,47 We performed a scratch assay and showed that SIRT1 was necessary for podocyte motility. Although the question of whether motile podocytes induce proteinuria and renal damage is still controversial, 8,41 it is widely accepted that the reorganization of actin cytoskeleton is necessary for podocyte migration.…”
Section: Discussionmentioning
confidence: 99%
“…45 Mutations of actin-binding proteins, such as a-actinin-4 or CD2AP, lead to podocyte injury because of disorganization of the actin cytoskeleton and disruption of its filtration barrier. 41,46,47 We performed a scratch assay and showed that SIRT1 was necessary for podocyte motility. Although the question of whether motile podocytes induce proteinuria and renal damage is still controversial, 8,41 it is widely accepted that the reorganization of actin cytoskeleton is necessary for podocyte migration.…”
Section: Discussionmentioning
confidence: 99%
“…The integrity of this barrier to maintain ultrafiltration of plasma depends on the proper expression and signaling of the components of the slit diaphragm (16)(17)(18). Several mutations in the gene that encodes nephrin (NPHS1), and other components of the slit diaphragm complex, have been described in patients with congenital nephrotic syndrome (14,19).…”
Section: Magi-2/s-scam | Glomerulosclerosismentioning
confidence: 99%
“…136,161 Proposed etiologic agents in ANCA disease include environmental toxins such as silica and infectious agents, including Gram-positive (S. aureus) and Gram-negative (Fim H adhesins) bacteria, viral infections, and several drugs. 122,[124][125][126][127][128] There also have been significant but low-level associations with potential susceptibility genes and their polymorphisms, including ANCA antigens, HLA, immune response proteins, Fc receptors, cytokines and others, but no high-level associations have been described, 163 other than DRB1*15 in African Americans. 164 The relatively frequent observation of ANCA antibodies in other autoimmune glomerular diseases including anti-GBM disease, lupus, and membranous nephropathy suggests that common etiologic or susceptibility factors may be present (Table 1).…”
Section: T Cellsmentioning
confidence: 99%